BIOLOGICAL ACTIVITIES OF EXTRACTIVES OF SOME ALPINIA AND HEDYCHIUM SPECIES - Nuntawong, Nuchnipa (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Air-dried rhizomes of A. malaccensis, A. galanga and H. gardnerianum were successively extracted with hexane, dichloromethane and methanol at room temperature and the solvent evaporated under reduced pressure to give hexane extract (2.02, 1.86 and 2.17 %), dichloromethane extract (1.92, 2.20 and 2.45 %) and methanol extract (1.48, 1.72 and 1.80 %). The crude extracts were evaluated for antiplasmodial, antimycobacterial and cytotoxic activities. The results showed that the hexane and dichloromethane extracts of all species exhibited antimycobacterial activity against Mycobacterium tuberculosis, with the hexane and dichloromethane extracts of A. galanga showing the strongest activity (MIC 0.39 ìg/ml). Only the hexane and dichloromethane extracts of A. galanga showed antiplasmodial activity against Plasmodium falciparum (IC50 3.74 and 6.04 ìg/ml, respectively). For cytotoxicity, the hexane and dichloromethane extracts of A. galanga and H. gardnerianum exhibited significant activity against the KB, BC and NCI-H187 cancer cell lines. However, the methanol extract of all species were inactive in all tests.